Assurance in Administrative Procedure - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Assurance is one of the novelties in the new Serbian Administrative Procedure Act, passed in 2016. Assurance is a written act through which a competent authority accepts the obligation to issue a certain administrative act, at the request of the party. Legal nature of this act is quite unclear and disputable. Legal theory usually asks itself whether this act can also be considered as an administrative act, or not. In order to answer this question, specific regulations on assurance must be analysed in domestic and comparative law. After this analyse has been done, we can conclude that these regulations are contradictory and the features of the assurance do not correspond to those of an administrative act.
Keywords: assurance, administrative act, acts of the administration, interpretation of the law, administrative procedure